Consider Tiffany historical sketch - Tiffany, Consider, 1733-1796.; Carter, Clarence Edwin, 1881-1961.
Historical sketch of the early Indian wars in America, 1600s; wars between England, France, and Spain, 1676-1763; relations between the American colonies and Great Britain, 1763-1775; the American Revolution, 1775-1783; and the postwar period, 1783-1796. Also includes a list of the monarchs of Great Britain and a description of the popes, emperors, and kings of France and England. Includes an account of Nathan Hale's service and capture as a spy during the American Revolution. Includes a typewritten transcript of the historical sketch by Clarence Edwin Carter.
Typewritten transcript available.
In part, typewritten transcript produced from the original in the possession of the Tiffany family.
Tory storekeeper of Connecticut.
Collection material in English.
Keywords: Hale, Nathan, -- 1755-1776.; American loyalists; Emperors; Indians of North America -- Wars -- 1600-1750.; Kings and rulers; Popes; Queens -- Great Britain; Spies -- United States; Europe -- History -- 1648-1789.; Europe -- History, Military -- 1648-1789.; France -- Foreign relations -- Great Britain; France -- Foreign relations -- Spain; France -- History; France -- Kings and rulers; Great Britain -- Colonies -- America; Great Britain -- Foreign relations -- France; Great Britain -- Foreign relations -- Spain; Great Britain -- Foreign relations -- United States; Great Britain -- History -- 1485-; Great Britain -- Kings and rulers; Spain -- Foreign relations -- France; Spain -- Foreign relations -- Great Britain; Spain -- History; United States -- Foreign relations -- Great Britain; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Secret service; United States -- History -- 1783-1815.; Merchants